The biogeography of Plantago ovata Forssk. (Plantaginaceae) - Meyers, Stephen C.
Plantago ovata Forssk. (Plantaginaceae) is a winter annual species which, in North America, inhabits desert and Mediterranean habitats of the southwest United States, northwest Mexico and the Channel Islands of California and Mexico. In the eastern hemisphere P. ovata inhabits desert regions ranging from the Canary Islands, across northern Africa to western India. The wide disjunction between P. ovata in the western and eastern hemispheres poses an interesting question as to the origin and biogeography of the species. Previous authors have hypothesized that P. ovata was introduced to North America over the Bering land bridge, from Asia, during the Miocene, or introduced anthropogenically from Europe during the 18th century by Spanish settlers. In this study we examined sequence data from the chloroplast trnL-trnF, trnS-trnG and psbA-trnH regions, the nuclear ribosomal internal transcribed spacer (ITS) and a region 5' of the TCP region of a CYCLOIDEA gene. Using a molecular clock based on an ITS calibration within the Plantago genus, and a clock for plant chloroplast, we date a non-anthropogenic introduction event, from the Old World to North America, approximately 200,000-650,000 years ago. This is consistent with a Pleistocene origin, and does not support a Miocene origin of the disjunction. Based on a morphological survey of 552 specimens, from throughout the world range of P. ovata, we suggest the recognition of four subspecific taxa. Molecular phylogenetic analysis of chloroplast DNA and nuclear ribosomal DNA ITS sequences support this taxonomic treatment. Furthermore, phylogenetic sequences of the CYCLOIDEA gene support the morphological data. Both suggest the origin of North American P. ovata as a result of hybridization between Old World P. ovata varieties. This event provides further evidence that hybridization may serve as a predictor of invasiveness in plants.